A SEMIOTIC ANALYSIS OF K-POP’S SELECTED MUSIC VIDEOS: THE STUDY OF THE KOREAN WAVE AS A GLOBAL PHENOMENON - Widya Sabrina (Universitas Bandar Lampung, 2023)
The purpose of this study is to determine the semiotic forms of the Korean wave in some K-Pop Music Videos. Semiotics is described as the study of signs. The videos studied were “Idol” by BTS, “Daechwita” by Agust D, “Hangover” by Psy and Snoop Dogg, “Pink Venom” by Blackpink and “Baam” by Momoland. I focused on the sign of denotation, connotation, and myth in these videos by using Roland Barthes’ theory. This research used a descriptive qualitative method. Data gathering was done by doing document analysis. There are 30 signs collected that were analyzed through interactive analysis of Miles and Huberman's theory involved data reduction, data display, and conclusion drawing or verification were carried out significantly. Based on the analysis done, it can be affirmed that music videos can be analyzed using Roland Barthes’ theory. The results find that the visual images communicate implied meaning conveyed through the pictures. It shows many signs related to the Korean Wave. For instance, hanbook, hangul, hoesik, Ilwol Obongdo, Pungmul, yangban, place, makeup, food, hairstyle, traditional musical instruments and accessories. All signs which were found in all 30 frames helped the video build the story of the song and deliver the intended message to the audience. It is related to the global phenomenon of the Korean Wave. Through these music videos, it can be a medium to attract viewers and advertise the Korean Wave to become a global phenomenon